Strengthening the social and emotional skills of pre-schoolers with mental health and developmental challenges in inclusive early childhood education and care settings: a narrative review of educator-led interventions. Issue 15 (18th November 2021) - Blewitt, Claire; O'Connor, Amanda; May, Tamara; Morris, Heather; Mousa, Aya; Bergmeier, Heidi; Jackson, Kylie; Barrett, Helen; Skouteris, Helen
ABSTRACT: Mental health and developmental challenges that emerge in early childhood can be associated with difficulty in social interactions and behavioural regulation. With educational policies increasingly promoting inclusion in early learning settings, educators are being called upon to support children's social-emotional competence through evidence-informed practice. A narrative review was undertaken to explore the breadth and summarize research findings related to educator-led Tier 3 social and emotional learning intervention for children with diagnosed mental health conditions or developmental delays. Nineteen evaluation studies were reviewed and synthesized into four themes: (i) instruction embedded into daily routines and activities; (ii) direct skill instruction; (iii) peer-mediated interventions; and (iv) individualized assessment-based approaches. Interventions targeted children with neurodevelopmental disorders, and developmental, social and communication delays, with findings suggesting improvement in children's social skill during or post intervention. Evidence of maintenance and generalization were, however, inconsistent. There is a paucity of peer-reviewed research examining interventions for young children experiencing anxiety or mood disorders.